2009
DOI: 10.1093/nar/gkp130
|View full text |Cite
|
Sign up to set email alerts
|

The quadruplex r(CGG)n destabilizing cationic porphyrin TMPyP4 cooperates with hnRNPs to increase the translation efficiency of fragile X premutation mRNA

Abstract: The 5′ untranslated region of the FMR1 gene which normally includes 4–55 d(CGG) repeats expands to > 55–200 repeats in carriers of fragile X syndrome premutation. Although the levels of premutation FMR1 mRNA in carrier cells are 5–10-fold higher than normal, the amount of the product FMR protein is unchanged or reduced. We demonstrated previously that premutation r(CGG)n tracts formed quadruplex structures that impeded translation and lowered the efficiency of protein synthesis. Normal translation could be res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 35 publications
3
66
0
Order By: Relevance
“…In a more recent NMR study, G/G mismatches were shown to exist in a dynamic equilibrium between the anti-and syn-conformations required to form two symmetric hydrogen bonds between the N1 and carbonyl oxygen atoms of two guanines (31). The CGG repeats were also reported to form G-quadruplexes in both RNA (11)(12)(13) and DNA (14,15). In the current study, we analyzed the structural features of CGG and other types of CNG repeats under identical conditions using biochemical and biophysical methods.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent NMR study, G/G mismatches were shown to exist in a dynamic equilibrium between the anti-and syn-conformations required to form two symmetric hydrogen bonds between the N1 and carbonyl oxygen atoms of two guanines (31). The CGG repeats were also reported to form G-quadruplexes in both RNA (11)(12)(13) and DNA (14,15). In the current study, we analyzed the structural features of CGG and other types of CNG repeats under identical conditions using biochemical and biophysical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, TMPyP4 destabilized the G-quadruplex of both the DNA and the RNA (CGG)n repeats of FMR1, associated with premutation expansions of fragile X syndrome, fragile X-associated tremor ataxia, and fragile X premature ovarian insufficiency (34 -36). Disruption of both RNA G-quadruplexes (MT3-MMP and FMR1) by TMPyP4 led to enhanced levels of translation in model systems (33,35). Here we report the binding of TMPyP4 to the ALS-FTD r(GGGGCC)8 repeat using gel mobility shift assays, CD spectroscopy, and UV spectroscopy.…”
mentioning
confidence: 88%
“…One possibility to explain this paradox is that the CGG expansion in the 5'-UTR of the transcript hampers the initiation of translation at the ribosome, possibly through the formation of quadruplex CGG secondary structures. 26 The cellular mechanisms that result in enhanced transcription of Fmr1 are unknown at present. Changes in the levels of Fmrp in the brain also seem to be brain region-specific with significant reductions in many regions of the brain, although expression remains relatively high in the hippocampus.…”
Section: Molecular Findingsmentioning
confidence: 99%